It takes a village to raise a child: Building social capital in safe and cohesive neighbourhood - Sheau Tsuey Chong, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
A vibrant and close-knit community is always associated with norms of trust and reciprocity with friendly neighbours in order to produce generalised social capital for the wider society. The researcher argues that the experience of long term interaction among neighbours, neighbourhood safety and cohesion and an active neighbourhood environment all contribute to social capital among neighbours. As a result, young people become more trusting in and reciprocative with people in general. Young Australians and permanent residents aged 16 to 25 (n=283) participated in this study through an online survey. The findings support previous literature, which found cohesive neighbours are more trusting than less cohesive neighbours. The results also indicate that the young people who perceived their neighbourhood as safe were relatively more trusting than those who perceived their neighbourhood as less safe. These suggest that creating neighbourhood „togetherness‟ and preventions of crime promotes could promote more neighbourhood social capital. In turn, young people enjoy more generalised social capital in the wider society